Tansiq Empowerment Leadership: An Approach To Empowerment Leadership Theory And Islamic Value To Improve Police Performance - Ayu, Ratih Candra; Pranaditya, Ari; Dewantoro, Bambang; Prasetiyo, Alfian Yudha (UP2MF Fakultas Ekonomi dan Bisnis, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2022)
Research on an individual's behavior and attitudes has been widely discussed and comes with various results when it comes to leadership styles. We propose a change in people's attitudes, optimistic attitudes, cooperation for performance improvements to bridge the gap. The purpose of this paper is to analyze the relationship between leadership empowerment and the effort to strength ten relationships or synergy between members of Jepara Police Department with a high vs low level of optimism. The questionnaire-based survey wil be conducted on 131 (one hundred and thirty-one) Jepara Police Officer Personnel. Many previous studies have explored the factors that cause the lack of cooperative relationships between leader and members but none approached with the perspective of Islamic values. Thus, this paper offers the concept as a foundation for improving the Police performance, especially the Jepara Police through Tansiq Empowerment Leadership. The authors argue that the absence of Tansiq and Optimism in improving police performance results in an absence of confidence, and a strong emotional connection between leader and members which might jeopardizing the achiement of organization's objectives. Therefore, tansiq is required in order to harmonize relationship and increase cooperation and coordination between leader and members